Postpartum Depression: What We Need To Know - Rizqie Putri Novembriani (STIKes Kepanjen, 2022)
A series of events from pregnancy, labor, and the birth of a baby is both a joyful and challenging time for women and their partners. Therefore, women are prone to experiencing mental health problems. One example of a mental health problem that is commonly experienced by mothers after giving birth is postnatal depression, with an estimated prevalence ranging from 9-20%. Postpartum depression should not be overlooked since a depressed mother will have a hard time carrying out her daily activities, which include her role as a mother or wife, thus negatively impacting family and other social relationships, if not diagnosed and treated. Women suffering from postpartum depression may become less attached to their children and even have negative attitudes toward them in some cases. These issues can adversely impact maternal-infant interactions, resulting in poor cognitive, behavioral, and social child development. Postpartum depression is treatable using either non-pharmacological or pharmacological methods. If the root cause of postpartum depression can be determined, treatment should focus on resolving the underlying issue. Screening for and treatment of postpartum depression should be integrated into maternal health care in public health facilities.